species pool concept as a framework for studying patterns of plant diversity - Zobel, Martin; Scheiner, Sam (Journal of vegetation science, 2016)
Co‐existence theories fail to adequately explain observed community patterns (diversity and composition) because they mainly address local extinctions. For a more complete understanding, the regional processes responsible for species formation and geographic dispersal should also be considered. The species pool concept holds that local variation in community patterns is dependent primarily on the availability of species, which is driven by historical diversification and dispersal at continental and landscape scales. However, empirical evidence of historical effects is limited. This slow progress can be attributed to methodological difficulties in determining the characteristics of historical species pools and how they contributed to diversity patterns in contemporary landscapes. A role of landscape‐scale dispersal limitation in determining local community patterns has been demonstrated by numerous seed addition experiments. However, disentangling general patterns of dispersal limitation in communities still requires attention. Distinguishing habitat‐specific species pools can help to meet both applied and theoretical challenges. In conservation biology, the use of absolute richness may be uninformative because the size of species pools varies between habitats. For characterizing the dynamic state of individual communities, biodiversity relative to species pools provides a balanced way of assessing communities in different habitats. Information about species pools may also be useful when studying community assembly rules, because it enables a possible mechanism of trait convergence (habitat filtering) to be explicitly assessed. Empirical study of the role of historic effects and dispersal on local community patterns has often been restricted due to methodological difficulties in determining habitat‐specific species pools. However, accumulating distributional, ecological and phylogenetic information, as well as use of appropriate model systems (e.g. archipelagos with known biogeographic histories) will allow the species pool concept to be applied effectively in future research.